(untitled) (REMUNOM, 2023)
Bullying is a serious and recurring problem in labor relations, causing numerous inconveniences to those who suffer. It is characterized by abusive behavior directed at the worker, as well as exposure to embarrassing and humiliating situations and, most of the time, stem from authoritarian hierarchical relationships, injuring the dignity of the human person. Objective: to discuss moral harassment, intending to identify the actions that constitute such harassment, evaluating the relevance and consequences when comparing with the victim’s dignity. The study emphasizes the principle of human dignity, defended by the Federal Constitution of 1988, since, with the practice of harassment, the aforementioned principle is violated. Methodology: Bibliographic research and the inductive method were used to propose a literature review research, approaching different aspects regarding moral harassment in the work relationship. Results: after analyzing the practice of harassment as well as the damages to the victim. There are resulting cases of harassment in the offices of companies and work institutions has been increasingly common in today’s world. Therefore, it is important to monitor their physical and psychological health, and that the harasser is penalized for abusive conduct according to legal provisions.